A study on reducing energy consumption of residential building using shading devices in Pokhara, Nepal - Kandel, Samikshya; Thapa, Luna; Karn , Abhishek; Babu Acharya, Shital (Journal of Innovations in Engineering Education, 2024)
Overall, around 40% of the world’s energy is consumed by the building sector. Energy consumption can be reduced by passive design strategies in the buildings. Among them, shading devices are one of the effective passive design strategies that can significantly reduce solar radiation and heat gain in buildings. This study explored the effects of different types of external shading devices for the reduction of energy consumption on a residential building located in Pokhara, Nepal, and proposed the optimal shading device based on computer simulations. This study uses Autodesk Ecotect Analysis 2011 as a simulation tool. The results of the simulations demonstrate that the horizontal double inclined shading device is most effective in case of saving heating load which is 31.39 % lower than base case. And egg crate shading device is the effective one in case of cooling load annually which is 16.23% lower than the base case. For overall consideration of heating and cooling load annually, the most effective shading device is horizontal double inclined which is 12.37 % less than the base case. Even without shading devices, a west-facing orientation is the most efficient, indicating the significance of orientation in energy load management.